Leflunamide Induced Pneumonitis in Rheumatoid Arthritis - A Case Report and Review of Literature - Mojumdar, Sumon Kanti; Islam, Md Nazrul; Ahmedullah, Abul Khair; Shahin, Md Abu; Hassan, Md Masudul (Bangladesh Medical Journal, 2017)
A 51 year old woman while treated on methotrexate (MTX) and leflunomide (LEF) for rheumatoid arthritis (RA), developed exertional breathlessness and undue tiredness followed by fever and cough, at her 11 years of suffering. Her respiratory symptoms developed around 12 weeks after leflunomide intake. She improved with steroid treatment. The Leflunomide (LEF) induced interstitial pneumonitis is an uncommon condition in absence of prior lung disease but potentially fatal. We report a case of Leflunomide (LEF) induced interstitial pneumonitis. Bangladesh Med J. 2017 Jan; 46 (1): 38-40